Institutional Collaboration on MOOCs in Education—A Literature Review - Anne-Mette Nortvig (Athabasca University Press, 2017)
This literature review seeks to outline the state of the art regarding collaboration between educational institutions on Massive Open Online Courses (MOOCs) launched in Europe and in the US for the past 10 years. The review explores enablers and barriers that influence national institutional MOOC collaboration, and looks into how existing knowledge about institutional collaboration on e-learning can be used in MOOC collaboration. The review is based on a literature search in databases and on snowballing techniques. It concludes that collaboration on MOOCs can be advantageous in terms of ensuring quality and innovation in the common learning designs, and that—in order to succeed—such projects need strategic and institutional support from all partners involved. Moreover, the review points out barriers concerning the reluctance of individual institutions to engage in national collaboration due to fear of potential loss of their own national branding and the teachers’ hesitancy or passive resistance to new educational platforms and formats.